Effect of mono- and dicationic ionic liquids on the viscosity and thermogelation of methylcellulose in the semi-diluted regime. (15th June 2019) - Isa Ziembowicz, Francieli; de Freitas, Darcson Vieira; Bender, Caroline Raquel; dos Santos Salbego, Paulo Roberto; Piccinin Frizzo, Clarissa; Pinto Martins, Marcos Antonio; Reichert, José Miguel; Santos Garcia, Irene Teresinha; Kloster, Carmen Luisa; Villetti, Marcos Antonio
Graphical abstract: Highlights: Methylcellulose (MC)/imidazolium ionic liquids (ILs) mixtures were prepared. The ILs increase the viscosity and change the rheological behavior of MC solutions. The ILs display transition from the salt-out to the salt-in on the gelation temperature. The presence of ILs (conventional or bolaform) decrease the gel strength. The interaction MC/ILs depends on hydrophobicity and type of ILs (mono or dicationic). Abstract: Thermoreversible hydrogels are suitable in food products in order to improve texture and in biomedical applications as drug delivery vehicles. The properties of hydrogels affect their performance in those applications. In this paper, it is presented the effect of mono- (Cn MIMBr) and dicationic (Cn (MIM)2 Br2 ) imidazolium ionic liquids (ILs) on the viscosity and gelation of methylcellulose (MC) using rheology, micro differential scanning calorimetric and small angle X-ray scattering (SAXS) techniques. Results show that the ILs affect the pattern of the sol-gel transition and display transition from the salt-out to the salt-in on the gelation temperature, decrease the gel strength and increase viscosity of MC solutions. This behavior can be explained by hydrophobic interaction between the ILs and the MC, which depends of the alkyl chain length of the ILs, type of ILs (conventional or bolaform) and the range of ILs concentration. In general, the presence of ILs decrease the MC gel strength, while dicationic ILs hampers their association on MC in comparison with monocationic ones. The findings highlight the role of ILs on gelation of MC opening possibilities for the design of new complex formulations.